To divide the fractions \( \frac{3x}{16} \) by \( \frac{3x-9}{20} \), you can multiply by the reciprocal of the second fraction.
This means:
\[ \frac{3x}{16} \div \frac{3x - 9}{20} = \frac{3x}{16} \times \frac{20}{3x - 9} \]
Now, we can multiply the fractions:
\[ \frac{3x \cdot 20}{16 \cdot (3x - 9)} = \frac{60x}{16(3x - 9)} \]
Next, we simplify this expression.
-
Simplify \( 60x \) and \( 16 \): \[ \frac{60x}{16(3x - 9)} = \frac{15x}{4(3x - 9)} \]
-
Factor \( 3x - 9 \) in the denominator: \[ 3x - 9 = 3(x - 3) \]
Substituting this back, we have: \[ \frac{15x}{4 \cdot 3(x - 3)} = \frac{15x}{12(x - 3)} \]
-
Now, simplify \( \frac{15x}{12(x - 3)} \): \[ \frac{15x}{12(x - 3)} = \frac{5x}{4(x - 3)} \]
Thus, the simplified answer is:
\[ \frac{5x}{4(x - 3)} \]